Perbandingan Efektivitas Ekstrak Sereh dengan Temulawak dalam Menghambat Pertumbuhan Streptococcus Mutans - Sri Yasa Hasibuan; Benarivo Timothy G; Cindy Amallia P; Mangatas H.P Hutagalung; Suci Erawati (Jurnal Ilmiah Kesehatan Sandi Husada, 2021)
Introduction; Streptococcus mutans is the main pathogenic bacteria that cause caries, caries treatment can be done traditionally with medicinal plants, including lemongrass and ginger. Aim; determine the comparison of the effectiveness of citronella leaf extract with ginger extract against Streptococcus mutants. Method; metabolic experimental research with a posttest-only control group design. Data collection by measuring the diameter of the zone of inhibition using shear calipers. Data were analyzed using a one-way ANOVA test. Results; showed that the average inhibitory diameter of 20% citronella extract was 12.00 ± 0.23, and 20% ginger extract was 9.00 ± 0.27 in inhibiting the growth of Streptococcus mutans, while the negative control (DMSO) had no inhibition. The conclusion is that there is a difference in the effectiveness of 20% citronella extract (Cymbopogon nardus) and 20% Curcuma (Curcuma xanthorrhiza) in inhibiting the growth of Streptococcus mutants.